Clinical and Dynamic Features of Comorbidal Course of Alcoholism and Schizophrenia (Eurasian Medical Research Periodical, 2022)
Researchers emphasize the close relationship of factors that determine the onset and development of mental illness for people with comorbid forms of substance abuse disorders. The comorbid course of alcoholism and mental disorders has features in the diagnosis, adequate treatment, clinical examination, because are considered at the junction of two specialties